Dampak Bullying terhadap Psikologi Peserta Didik - Mu'ammar Rojai; Munali Munali; Muhammad Alif Hidayatullah (YASIN, 2026)
Although bullying remains a serious problem in educational settings, this practice often appears in forms that are considered normal, such as ridicule, social exclusion, and pressure from peers and seniors. This study aimed to analyze the impact of bullying and identify the most dominant dimension affecting the psychological condition of students at Madrasah Tsanawiyah Jam’iyyah Islamiyyah Pondok Aren, South Tangerang. This study used a mixed-methods approach involving 60 students in January–February 2026. The research instrument consisted of 20 statement items covering four dimensions, namely verbal bullying, physical bullying, social bullying, and seniority. Data were collected through questionnaires and analyzed using percentage techniques. The results showed that verbal bullying had the highest percentage at 63%, followed by social bullying at 52%, seniority at 49%, and physical bullying at 46%. These findings indicate that verbal bullying is the most dominant dimension affecting students’ emotional condition, as reflected in the emergence of anxiety, sadness, low self-esteem, and decreased self-confidence. This study concludes that bullying, particularly in verbal form, has a significant impact on students’ psychological condition. These findings contribute to strengthening the study of the psychological impact of bullying in the madrasah environment and provide practical implications for schools to strengthen bullying prevention programs, guidance and counseling services, and the cultivation of character values and religiosity in order to create a safe and supportive learning environment.